The first ten years of selby gardens - Luer, Carlyle A (Lankesteriana: International Journal on Orchidology, 2014)
In her will, Marie Selby left her home and grounds to be used as a “botanical garden” at the discretion of the directors of Palmer Bank. The property was zoned for high-rises, but opposition to a botanical garden was overcome. Cal Dodson, Professor of Botany at the University of Miami, was a chosen as a director. The Gardens soon acquired more grounds and staff. A volunteer program was begun, and volunteers contributed vastly to our rapid growth. Our many accomplishments include the quarterly Bulletin, first appearing in spring 1974, and the scientific journal, Selbyana, first published in January 1975. The growth of the Gardens would inevitably accelerate with the great infrastructure put in place during our first ten years